Bispecific T-Cell Engagers Targeting Membrane-Bound IgE - Aleksandra Rodak (MDPI AG, 2021)
The increased incidence of allergies and asthma has sparked interest in IgE, the central player in the allergic response. Interaction with its high-affinity receptor FcεRI leads to sensitization and allergen presentation, extracellular membrane-proximal domain in membrane IgE can act as an antigen receptor on B cells, and the interaction with low-affinity IgE receptor CD23 additionally influences its homeostatic range. Therapeutic anti-IgE antibodies act by the inhibition of IgE functions by interfering with its receptor binding or by the obliteration of IgE-B cells, causing a reduction of serum IgE levels. Fusion proteins of antibody fragments that can act as bispecific T-cell engagers have proven very potent in eliciting cytotoxic T-lymphocyte-mediated killing. We have tested five anti-IgE Fc antibodies, recognizing different epitopes on the membrane-expressed IgE, for the ability to elicit specific T-cell activation when expressed as single-chain Fv fragments fused with anti-CD3ε single-chain antibody. All candidates could specifically stain the cell line, expressing the membrane-bound IgE-Fc and bind to CD3-positive Jurkat cells, and the specific activation of engineered CD3-overexpressing Jurkat cells and non-stimulated CD8-positive cells was demonstrated for 8D6- and ligelizumab-based bispecific antibodies. Thus, such anti-IgE antibodies have the potential to be developed into agents that reduce the serum IgE concentration by lowering the numbers of IgE-secreting cells.